Post-Pandemic Air Quality Assessment in the District of San Borja - Bejar-Calderon, Alejandro J.; Licapa-Redolfo, Gladys S. (LACCEI, 2024)
The objective of this research was to determine the degree of concentration of pollutants to evaluate post-pandemic air quality with respect to the year 2023. The research approach is descriptive, for which information from air quality monitoring and the meteorological station of the National Service of Meteorology and Hydrology of Peru (SENAMHI) located in the district of San Borja. The result indicated that, of the 6 parameters analyzed PM10; PM2.5; CO; NO2; SO2 and O3; They are within the range and half exceed the standard recommended by the Environmental Quality Standard for air DS N° 003-2017 MINAM. In that sense, PM-10 is exceeded in almost every month, reaching a maximum level of 220 μg/m3 in May, with ECA PM-10 being 100 μg/m3; in PM-2.5 in the months evaluated complies with the regulations, but in July it exceeds the concentration with 260 μg/m3 and the ECA for PM-2.5 is 50 μg/m3 and NO2 in June reaches 580 μg/m3 and the ECA establishes a value of 200 μg/m3, therefore it is concluded that particulate matter of 2.5 and 10 microns has a higher concentration throughout the study period. Furthermore, the results show the behavior of the measured parameters. It is recommended to establish rapid response protocols for high air pollution events, such as temporary traffic restrictions, closure of polluting sources and alerts to the population to suppress the disturbing issue of poor air quality.